Efficient synthesis of 4-substituted-ortho-phthalaldehyde analogues: toward the emergence of new building blocks - Moitessier, Clémence; Rifai, Ahmad; Danjou, Pierre-Edouard; Mallard, Isabelle; Cazier-Dennin, Francine (Beilstein Journal of Organic Chemistry, 2019)
4-Methoxy-ortho-phthalaldehyde and 4-hydroxy-ortho-phthalaldehyde are potentially useful molecules for fluorimetric analysis of a variety of amines and for the elaboration of complex molecular architectures. Nevertheless, literature generally describes their synthesis in very low yield (below 5%), mainly due to the inefficiency of the last oxidation step. In this paper, we report a reliable synthesis of 4-substituted-ortho-phthalaldehyde analogues in 51% overall yield owing to the addition of a protecting step of the unstable key intermediate 4,5-dihydroisobenzofuran-5-ol. Oxidation and deprotection steps were also studied in order to provide an effective availability of these two dialdehyde compounds that may increase their future applications.
Keywords: demethylation; hydroxy group protection; 4-hydroxy-ortho-phthalaldehyde; ortho-phthalaldehyde; oxidation